PEMBELAJARAN SAINS UNTUK ANAK SD/MI DENGAN PENDEKATAN SAINTIFIK - Supriyati Supriyati (Jurusan PGMI FTIK IAIN Metro Lampung, 2015)
Learning is a process of the interaction of learners with educators and learning resources pada suatulingkungan belajar. At elementary school age children experience rapid growth both in the physicaland inteligensi. Science is knowledge that is verifiable by using scientific methods. The process skills andscientific attitude can be trained to learners to learn science. The nature of science is a product, processand scientific attitude. The process of learning with a scientific approach which touches three domainsare cognitive, affective and psychomotor. Results of study with scientific approach makes studentsproductive, creative, and innovative. Enhancement affective through the strengthening of attitudes,skills and integrated knowledge. Five basic learning experiences in the scientific approach is to observe,ask, gather information, associates, and communicate.